ROLE OF MEDIA IN PORTRAYAL OF GENDER STEREOTYPES: A QUALITATIVE STUDY ON HIGH SCHOOL STUDENTS PERCEPTIONS - Tanwar, Mimansa Singh; Ali, Adiba (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Through the lens of the high school students, this qualitative study explores perceived influence of media in shaping, reinforcing and challenging gender stereotypes. As shared by students described how media contributes to gender discourses in significant ways by portraying the normative gender ideas of masculinity and femininity. Using a thematic analysis approach, the paper examines the how students perceive, decode and respond to gendered messaged that are portrayed across social media, print, film and television platform. The study shows that gender stereotypes are not just passively absorbed, rather students actively engage in meaning making process in context to their social, personal and peer experiences. With review of literature highlighting the potential impact of media on adolescents’ perceptions of gender roles, the results highlight the importance of integrating media literacy and gender sensitive pedagogies in the educational spaces that enables students to critically challenge normative practices, assumptions and reconstruct inclusive understanding of gender.